Análise das internações por condições sensíveis à Atenção Primária em hospital de referência regional, SP/Brasil - Nunes, Karina Rubia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The World Health Organization has formalized its commitment to primary health care (PHC) in the late 70s in the Alma Ata Conference, when the stressed as a key tool for meeting the goal Health for All. In Brazil, the Unified Health System (SUS) is a state policy and articulates the APS clinical actions of promotion, prevention, treatment and rehabilitation. These actions are based on the principles of universality, comprehensiveness and equity, and have as organizational principles Decentralisation, Regionalisation, Hierarchy and Social Participation. To the growing effort to improve the quality of PHC in the country, evaluative mechanisms have been widely used to improve services, the health actions and programs established at different levels of care. The evaluation of Admissions by Primary Care Sensitive Conditions (ICSAP) aims to identify gaps in access and quality of primary services offered to the population. The aim of this study is to analyze the ICSAP in a regional referral hospital in the period 2008-2012. The thesis consists of three studies, namely: a qualitative nature, literature integrative review; two quantitative, transversal and hospital-based. The main characteristics of APS associated with lower ICSAP rates were high coverage of the Family Health; health clinics located in urban areas; doctors in urban areas; rural clinics in areas with professional shortages; most doctor's length of stay in the Family Health team consultations in primary care in the previous year; consultations in primary care with quality and greater physician / inhabitant density; implementation of drug distribution program for over 65 years; financial incentives for primary care and funding for Indian Health Service. The hospital performed 49,476 hospitalizations in the 2008-2012 period, and of these only 7.43% were due Sensitive Conditions Primary. The three main causes of hospitalization were: Cerebrovascular diseases (27.3), Bacterial ...

A Organização Mundial da Saúde formalizou seu compromisso com a Atenção Primária à Saúde (APS), no final da década de 70 na Conferência de Alma Ata, quando à destacou como ferramenta chave para o cumprimento da meta Saúde para Todos. No Brasil, o Sistema Único de Saúde (SUS) é uma política de Estado e a APS articula ações clínicas de promoção, prevenção, tratamento e reabilitação. Essas ações são pautadas nos princípios da universalidade, integralidade e equidade, e possuem como princípios organizativos a Descentralização, Regionalização, Hierarquização e a Participação Social. Frente ao crescente esforço para melhoraria da qualidade da APS no país, mecanismos avaliativos vêm sendo amplamente utilizados para a melhoria dos serviços, das ações em saúde e de programas, instituídos em diferentes níveis de atenção. A avaliação das Internações por Condições Sensíveis à Atenção Primária (ICSAP) tem por objetivo identificar falhas no acesso e na qualidade dos serviços primários ofertados a população. O objetivo deste estudo é o de analisar as ICSAP em um hospital de referência regional, no período de 2008-2012. A tese é composta por três estudos, sendo eles: um de natureza qualitativa, de revisão integrativa de literatura; dois de natureza quantitativa, transversais e de base hospitalar. As principais características da APS associadas às menores taxas de ICSAP foram: elevada cobertura da Saúde da Família; localização de clinicas de saúde em áreas urbanas; médicos na área urbana; clínicas rurais em áreas com escassez profissional; maior tempo de permanência do médico em equipe de Saúde da Família realização de consultas na atenção primária no ano anterior; consultas em atenção primária com qualidade e maior densidade médico/habitante; implantação de programa de distribuição de medicamentos para maiores de 65 anos; incentivo financeiro à atenção...
Keywords: Cuidados primários de saúde; Cuidados médicos - Avaliação; Indicadores de qualidade em assistência à saúde; Hospitalização; Quality Indicators, Health Care